Oxidation of sputtered metallic Sn thin films using N2 atmospheric pressure plasma jets. (2nd January 2015) - Lin, Guan-Wei; Jiang, Yu-Hao; Kao, Peng-Kai; Chiu, I-Chung; Wu, Yu-Han; Hsu, Cheng-Che; Cheng, I-Chun; Chen, Jian-Zhang
Abstract: We investigated the oxidation of sputtered metallic Sn thin films annealed by N2 atmospheric pressure plasma jets (APPJs) with and without the introduction of ambient air to the reaction. As the APPJ annealing duration increased, the metallic Sn first oxidized into SnO, and then, a metallic Sn phase reappeared owing to the disproportionation reaction 4SnO → Sn3 O4 + Sn → 2Sn + 2SnO2 . The involvement of O2 from the ambient air led to more reactive oxidation of the thin films. APPJ annealing increased the band gap to ∼2.6–2.7 eV. All the annealed films show conductivity with unstable readings of carrier types because of the mixed phases of Sn, SnO, and possibly, some SnO2 in the films.